2014
DOI: 10.1371/journal.pone.0102425
|View full text |Cite
|
Sign up to set email alerts
|

Liposome Reconstitution and Modulation of Recombinant Prenylated Human Rac1 by GEFs, GDI1 and Pak1

Abstract: Small Rho GTPases are well known to regulate a variety of cellular processes by acting as molecular switches. The regulatory function of Rho GTPases is critically dependent on their posttranslational modification at the carboxyl terminus by isoprenylation and association with proper cellular membranes. Despite numerous studies, the mechanisms of recycling and functional integration of Rho GTPases at the biological membranes are largely unclear. In this study, prenylated human Rac1, a prominent member of the Rh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 72 publications
0
17
0
Order By: Relevance
“… 7,8,37 Similarly, the presence of PIP 3 alone is insufficient to stimulate a robust association of the purified iDHPH domains of P-Rex1 with liposomes. 59 …”
Section: Regulation Of Subcellular Localizationmentioning
confidence: 99%
“… 7,8,37 Similarly, the presence of PIP 3 alone is insufficient to stimulate a robust association of the purified iDHPH domains of P-Rex1 with liposomes. 59 …”
Section: Regulation Of Subcellular Localizationmentioning
confidence: 99%
“…Like all GTPases, the Rac1 is under tight spatial control, which is mediated by guanine nucleotide exchange factors (GEFs) and GTPase-activating proteins (GAPs) that catalyse GTP exchange and hydrolysis, respectively [23]. Specific GEF allows Rac1 to be activated in specific signal transduction pathways and coordinate more elaborate responses to specific demands at localized cellular sites [26, 42]. In this study, we identified the exchange factor Vav2 as mediating autocrine VEGF and IL-8 signaling to Rac1.…”
Section: Discussionmentioning
confidence: 99%
“…This is achieved by a hypervariable region (HVR) (66) and a lipid anchor in their C-terminal tail at a distinct cysteine residue in the C AAX motif (C is cysteine, A is any aliphatic amino acid, and X is any amino acid) (67). RHOGDI is known to dislodge RHO proteins from the plasma membrane (68). As IQGAP1 also binds RHOGDI (20), it would be interesting to know whether IQGAP1 is a displacement factor for the RHOGDI complex with RAC1 or CDC42.…”
Section: Discussionmentioning
confidence: 99%